Spiritual assessment and spiritual care offerings as a standard of care in pediatric oncology: A recommendation informed by a systematic review of the literature. Issue 9 (29th April 2019) - Robert, Rhonda; Stavinoha, Pete; Jones, Barbara L.; Robinson, Jacob; Larson, Kara; Hicklen, Rachel; Smith, Blake; Perko, Kathleen; Koch, Kendra; Findley, Stephen; Weaver, Meaghann S.
Abstract: Children with cancer and their families experience shifts in spiritual wellness from diagnosis through treatment and survivorship or bereavement. An interdisciplinary team conducted a systematic review of quantitative and qualitative research on spiritual assessments, interventions, and outcomes in childhood cancer following PRISMA guidelines using a PROSPERO registered protocol. Thirty‐nine well‐designed studies were included in the final analysis. The findings from this systematic review indicate the need for early spiritual assessment with offering of continued support for the spiritual functioning of children with cancer and their families as a standard of care.